PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN CAROUSEL FEEDBACK SD NEGERI 03 JENGGAWAH - Noviana Mariatul Ulfa (Education Journal : Journal Educational Research and Development, 2017)
Learning model carousel feedback is one model of cooperative learning. Where during this process, students are required to work with each other to provide feedback on the questions posed by the teacher, then reflect on the feedback so as to produce an answer. This study aims to determine whether the application of learning model carousel feedback can improve student learning outcomes class VI SDN 03 Jenggawah on the material describe the symptoms (events) that occur in Indonesia and neighboring countries. Based on pretest results for carousel feedback model. Ie as many as 18 or 58.06% of students have high criteria and as many as 13 students or 41.94% have medium ability. As for learning outcomes after getting treatment with carousel feedback (posttest) model, learning outcomes have increased. Posttest data with carousel feedback model is 26 students or 83,87% having high learning achievement criteria, and 5 students or 16,13% who have criteria of medium earning outcomes, whereas no students have learning result criteria low.